Determination of La in ore using laser-induced breakdown spectroscopy combined with laser-induced fluorescence and standard addition method. Issue 10 (20th September 2022) - Li, Jiangtao; Tang, Zhiyang; Hao, Zhongqi; Huang, Zhijie; Zhu, Chenwei; Li, Qingzhou; He, Bing; Chen, Ji; Li, Xiangyou
Abstract : LIBS-LIF combined with SAM was used to reduce the self-absorption effect and matrix effect to achieve accurate determination of La in rare earth ore. Abstract : The detection of lanthanum (La) is of great significance for the mining of rare earth ore. However, the quantitative analysis results of La element in rare earth ore using Laser-induced breakdown spectroscopy (LIBS) are quite poor due to the matrix effect and self-absorption. Therefore, the LIBS assisted by Laser-induced fluorescence (LIBS-LIF) combined with the standard addition method (SAM) was proposed to improve the quantitative analysis performance of La element in rare earth ore. To demonstrate the superiority of this method, the detection results of La using LIBS, LIBS-LIF, LIBS combined with SAM and LIBS-LIF combined with SAM were compared. The result shows that the quantitative curve of using LIBS-LIF combined with SAM has good linearity, and the linear coefficient R 2 reaches 0.994. Moreover, the limit of detection (LoD) and RMSECV were 7.195 ppm and 0.0019 wt%, respectively. Furthermore, the relative error between the predicted concentration and the actual concentration is 0.26%. These results indicate that LIBS-LIF combined with SAM can effectively reduce the influence of matrix effect and self-absorption effect, and achieve the accuracy of La determination in rare earth ore.